INTERSTITIAL RENAL NECROSIS SYNDROM OF CALVES - Al-Sultan, I.I.; Youkhana , S.O.; Ismail, H.K. (The Iraqi Journal of Veterinary Medicine, 2021)
Interstitial renal necrosis syndrom (IRNS) was diagnosed in calves sloughtered in Mosul sloughter house. Gross and microscopical picture of 33 affected animals were described. The lesions were identified according topathomorpholgy of tissue reaction. Two patterns of tissue rections were observed. The lesions of the first pattern showed grossly an oval, greyish white translucent nodules on the surface of kidney. Microscopically, cells like lymphocytes and few plasma cells were aggregated in the interstitial tissue. The lesions of the second pattern comprised grossly a milliary yellowish-white nodules on the surface of the kidney and on cut sectionforming extention in the depth of the renal cortex. Microscopically, the infiltrated cells were mainly neutrophils, macrophages and few lymphocytes, the possible causes of this syndrom was discussed.